Dipylidium caninum in the twenty‑first century - Rousseau, Julieta (2022)
Funding text: The Global Health and Tropical Medicine centre is funded by the Fundacao para a Ciencia e a Tecnologia, I.P. (FCT) (GHTM-UID/Multi/04413/2013), Portugal. JR was supported by the Portuguese Ministry of Science, Technology and Higher Education (via FCT) through a Ph.D. grant (2021.04669.BD). AC was supported by a grant (PRT/BD/152100/2021) under the MIT/FCT program.